Infrared Spectrum of the Si3H8+ Cation: Evidence for a Bridged Isomer with an Asymmetric Three‐Center Two‐Electron SiHSi Bond. Issue 45 (17th September 2013) - George, Martin Andreas Robert; Savoca, Marco; Dopfer, Otto
Abstract The IR spectrum of Si3H8+ ions produced in a supersonic plasma molecular beam expansion of SiH4, He, and Ar is inferred from photodissociation of cold Si3H8+–Ar complexes. Vibrational analysis of the spectrum is consistent with a Si3H8+ structure (2+) obtained by a barrierless addition reaction of SiH4 to the disilene ion (H2SiSiH2+) in the silane plasma. In this structure, one of the electronegative H atoms of SiH4 donates electron density into the partially filled electrophilic π orbital of the disilene cation. The resulting asymmetric SiHSi bridge of the 2+ isomer with a bond energy of approximately 60 kJ mol−1 is characteristic for a weak three‐center two‐electron bond, which is identified by its strongly IR active asymmetric SiHSi stretching fundamental at about 1765 cm−1. The observed 2+ isomer is calculated to be only a few kJ mol−1 less stable than the global minimum structure of Si3H8+ (1+), which is derived from vertical ionization of trisilane. Although more stable, 1+ is not detected in the measured IR spectrum of Si3H8+–Ar, and its lower abundance in the supersonic plasma is rationalized by the production mechanism of Si3H8+ in the silane plasma, in which a high barrier between 2+ and 1+ prevents the efficient formation of 1+. The potential energy surface of Si3H8+ is characterized in some detail by quantum chemical calculations. The structural, vibrational, electronic and energetic properties as well as the chemical bonding mechanism are investigated for a variety of low‐energy Si3H8+ isomers and their fragments. The weak intermolecular bonds of the Ar ligands in the Si3H8+–Ar isomers arise from dispersion and induction forces and induce only a minor perturbation of the bare Si3H8+ ions. Comparison with the potential energy surface of C3H8+ reveals the differences between the silicon and carbon species.